Pengaruh Gaya Kepemimpinan Dan Disiplin Terhadap Motivasi Dan Implikasinya Pada Kinerja Karyawan Pt. Askrindo - Alwin dan Cicih Ratnasih (Fakultas Ekonomi Universitas Borobudur, 2015)
This study aims to determine the effect of the leadership style, discipline motivation and performance either partially or simultaneously at PT. Askrindo.. Total population in the study is a quantitative method. Total population in this human development resourch and the study sample research, counted as many as 108 respondance. The sampling technique using purposive sampling. The variable in this study is the independent variable (independent) consisting of leadership style, discipline motivation and performance and the dependent variable (dependent) is Audit quality.The results showed that the leadership style, discipline, motivation and performance effecting significant partially on PT. Askrindo. leadership style, dis style cipline motivation and performance effecting significant Simultaneously, leadership style, discipline, motivation and performance effecting significant effect on performance level determination coefficient to 81,6%.